The stray dog - Simont, Marc (HarperCollins Publishers, 2001)
When a little dog appears at a family picnic, the girl and boy play with him all afternoon. They name him Willy. At day's end they say good-bye. But the dog has won their hearts and stays on their minds. The following Saturday the family returns to the picnic grounds to look for Willy, but they are not alone-- the dogcatcher is looking for him, too!